Working-Class Men and Social Suffering in Contemporary Lithuania - Tereškinas, Artūras; Dryžaitė, Ieva (Sociologija. Mintis ir veiksmas, 2009)
This article focuses on Lithuanian working-class men’s social suffering. Analyzing 19 semi-structured interviews with working class men, it attempts to describe their everyday miseries and to expose social factors contributing to their oppression and domination. The interviews reveal that these men accept their inferior status in the social world. Older working-class men feel unappreciated by employers and co-workers. They are insufficiently integrated into and excluded from the labor market. Younger men are trapped in the unstable, low-salary and, in many cases, illegal jobs. They feel depoliticized, dominated and subordinated by the new forms of symbolic violence produced by the current social, economical and political system. These men’s social suffering and exclusion are also related to their sense of powerlessness. Not only is the sense of powerlessness but also the inability to resist it inherently shameful for the interviewed men. Thus, the working-class men’s “small miseries” can be explained not only by political instability, social disruption, physical and economic hardship but also by their subjective sense of powerlessness and despair. Stigma, indirect discrimination, isolation, depression, and anxiety – all contribute to ordinary suffering of these men.
Keywords: working-class men; social suffering; social exclusion; class; masculinity